Extracellular Vesicles, Tunneling Nanotubes, and Cellular Interplay: Synergies and Missing Links - Nawaz, Muhammad; Fatima, Farah (Frontiers in Molecular Biosciences, 2017)
The process of intercellular communication seems to have been a highly conserved evolutionary process. Higher eukaryotes use several means of intercellular communication to address both the changing physiological demands of the body and to fight against diseases. In recent years there has been an increasing interest in understanding how cell-derived nanovesicles, known as extracellular vesicles (EVs), can function as normal paracrine mediators of intercellular communication, but can also elicit disease progression and may be used for innovative therapies. Over the last decade a large body of evidence has accumulated to show that cells use cytoplasmic extensions comprising open-ended channels called tunneling nanotubes (TNTs) to connect cells at a long distance and facilitate the exchange of cytoplasmic material. TNTs are a different means of communication to classical gap junctions or cell fusions; since they are characterized by long distance bridging that transfers cytoplasmic organelles and intracellular vesicles between cells and represent the process of heteroplasmy. The role of EVs in cell communication is relatively well understood, but how TNTs fit into this process is just emerging. The aim of this review is to describe the relationship between TNTs and EVs, and to discuss the synergies between these two crucial processes in the context of normal cellular cross-talk, physiological roles, modulation of immune responses, development of diseases and their combinatory effects in tissue repair. At the present time this review appears to be the first summary of the implications of the overlapping roles of TNTs and EVs. We believe that a better appreciation of these parallel processes will improve our understanding on how these nanoscale conduits can be utilized as novel tools for targeted therapies.